Eugenia uniflora L. seed and pulp extracts: phytochemical profile, cytotoxic potential, antitumoral activity, and α-amylase and α-glucosidase inhibition capacity - Felipe Tecchio Borsoi; Beatriz da Silva Rosa Bonadiman; Filomena Marafon; Doralice Lobato de Oliveira Fischer; Margarete Dulce Bagatini; Aniela Pinto Kempka (Natural Product Research, 2023)

Valorisation of spent tire rubber as carbon adsorbents for Pb(II) and W(VI) in the framework of a Circular Economy - Maria Bernardo; Nuno Lapa; Filomena Pinto; Miguel Nogueira; Inês Matos; Márcia Ventura; Ana Maria Ferraria; Ana Maria Botelho do Rego; Isabel Maria Fonseca (Environmental Science and Pollution Research, 2023)
Spent tire rubber-derived chars and their corresponding H 3 PO 4 and CO 2 -activated chars were used as adsorbents in the recovery of Pb(II) ion and (W(VI)) oxyanion from synthetic solutions. The developed chars (both raw and activated) were thoroughly characterized to have insight about their textural and surface chemistry properties. H 3 PO 4 -activated chars presented lower surface areas than the raw chars and an acidic surface chemistry which affected the performance of these samples as they showed the lowest removals of the metallic ions. On the other hand, CO 2 -activated chars presented increased surface areas and increased mineral content compared to the raw chars, having presented higher uptake capacities for both Pb(II) (103–116 mg/g) and W(VI) (27–31 mg/g) ions. Cation exchange with Ca, Mg and Zn ions was appointed as a mechanism for Pb removal, as well as surface precipitation in the form of hydrocerussite (Pb 3 (CO 3 ) 2 (OH) 2 ). W(VI) adsorption might have been ruled by strong electrostatic attractions between the negatively charged tungstate species and the highly positively charged carbons’ surface. The results shown in this work allow concluding that the valorisation of spent tire rubber through pyrolysis and the subsequent activation of the obtained chars is an alternative and a feasible option to generate adsorbent materials with a high uptake capacity of critical metallic elements.

Phytochemical profiling, antidiabetic, antitumoral and cytotoxic potential of Psidium cattleianum Afzel. ex Sabine leaves of red variety - Yasmine de Melo Barradas; Felipe Tecchio Borsoi; Marina Volpato Dacoreggio; Liziane Schittler Moroni; Beatriz da Silva Rosa Bonadiman; Filomena Marafon; Clevison Luiz Giacobbo; Margarete Dulce Bagatini; Aniela Pinto Kempka (Natural Product Research, 2023)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Recovery of Cr(III) by using chars from the co-gasification of agriculture and forestry wastes - Delfina Godinho; Miguel Nogueira; Maria Bernardo; Diogo Dias; Nuno Lapa; Isabel Fonseca; Filomena Pinto (Environmental Science and Pollution Research, 2019)

An Integrated All-Atlantic Ocean Observing System in 2030 - Brad deYoung; Martin Visbeck; Moacyr Cunha de Araujo Filho; Molly O’Neil Baringer; CarolAnne Black; Erik Buch; Gabrielle Canonico; Paulo Coelho; Janice T. Duha; Martin Edwards; Albert Fischer; Jan-Stefan Fritz; et al. (Frontiers in Marine Science, 2019)

Study of the removal mechanism of aquatic emergent pollutants by new bio-based chars - Maria Manuel Serrano Bernardo; Catarina Alexandra Catanas Madeira; Nuno Carlos Lapa dos Santos Nunes; Diogo André Costa Messias Dias; Delfina Maria Barbosa Godinho; Maria Filomena de Jesus Pinto; Inês Alexandra Morgado do Nascimento Matos; Ana Paula Batista Carvalho; Isabel Maria de Figueiredo Ligeiro Fonseca (Environmental Science and Pollution Research, 2017)

Study of the co-pyrolysis of biomass and plastic wastes - Filipe Paradela; Filomena Pinto; Ibrahim Gulyurtlu; Isabel Cabrita; Nuno Lapa (Clean Technologies and Environmental Policy, 2009)

High-resolution comparative chromosome painting in the Arizona collared peccary (Pecari tajacu, Tayassuidae): a comparison with the karyotype of pig and sheep - Filomena Adega; Raquel Chaves; Andrea Kofler; Paul R. Krausman; Julio Masabanda; Johannes Wienberg; Henrique Guedes-Pinto (Chromosome Research, 2006)

Molecular cytogenetic analysis and centromeric satellite organization of a novel 8;11 translocation in sheep: a possible intermediate in biarmed chromosome evolution - Raquel Chaves; Filomena Adega; Johannes Wienberg; Henrique Guedes-Pinto; John S. Heslop-Harrison (Mammalian Genome, 2003)

The effect of spikelet position on the success frequencies of wheat haploid production using the maize cross system - Paula Filomena Martins-Lopes; Henrique Guedes-Pinto; Olinda Pinto-Carnide; John Snape (Euphytica, 2001)